The fasciclin‐like arabinogalactan protein family of Eucalyptus grandis contains members that impact wood biology and biomechanics. Issue 4 (10th February 2015) - MacMillan, Colleen P.; Taylor, Lynette; Bi, Yingdong; Southerton, Simon G.; Evans, Rob; Spokevicius, Antanas
Summary: Fasciclin‐like arabinogalactan protein (FLA) families have been identified and characterised in key plant species, with some members exhibiting functional specialization. Here we identify the FLA family of Eucalyptus grandis, and investigate the roles of three single‐FAS domain FLAs, with particular focus on secondary cell‐wall formation and wood properties. We use various in‐silico approaches to identify and characterise E. grandis genome FLAs, and perform phylogenetic comparisons with other species. For three key FLAs, we perform functional testing including promoter‐reporter and overexpression transgenic approaches using eucalypts, poplar and tobacco. Of the 18 eucalypt FLAs identified, several were specifically and highly expressed in stems. The specificity to stem xylem vessel and fibre development was demonstrated with EniFLA1 promoter:GUS studies in several species. Testing of select eucalypt FLAs resulted in altered wood development and properties, for example 35S: EgrFLA2 led to a 3 degree reduction in cellulose microfibril angle in eucalypt xylem fibres, and 35S: Egr FLA3 to a reduction in tobacco stem flexural strength. These results indicate that the eucalypt FLA family contains diverse members, and particular members with single FAS domains that are functionally specialized for secondary cell wall growth and properties. Abstract : Featured paper: see also the Commentary by Strauss & Myburg